Os benefícios e os custos da implantação do gerenciamento em projetos pequenos e médios de construção civil - Zanfelice, José Carlos (1994)
In this work are described the characteristics of the construction industry. The implementation of project management techniques in small and medium construction projects is analysed through the comparison of the benefits and costs. The success of such implementation is determined by the use of a measuring instrument called Project Implementation Profile.